2013
DOI: 10.1590/s1676-06032013000400032
|View full text |Cite
|
Sign up to set email alerts
|

Diet of two sit-and-wait lizards, Phyllopezus pollicaris (Spix, 1825) (Phyllodactylidae) and Hemidactylus mabouia (Moreau de Jonnès, 1818) (Gekkonidae) in a perianthropic area of Mato Grosso do Sul, western Brazil

Abstract: The dietary compositions of two sit-and-wait lizard species, Hemidactylus mabouia and Phyllopezus pollicaris, which co-occur over rocky substrate and vertical rock walls in a perianthropic area of western Brazil, were described. Both species showed a generalist feeding pattern, feeding mainly on insects. The most frequent prey items in the diet of P. pollicaris were Coleoptera, Araneae and Homoptera whereas the most important were Coleoptera and Homoptera, respectively. For H. mabouia the most frequent prey it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…Hemidactylus spp. are typically ambush predators of invertebrate prey who benefit from structurally simple habitats and aggregations of winged insects around artificial light sources [4,[49][50][51]. Conversely, P. pulcher may have a more active approach to encountering dispersed insect prey amongst structurally diverse rock habitat (RW pers obs).…”
Section: Discussionmentioning
confidence: 99%
“…Hemidactylus spp. are typically ambush predators of invertebrate prey who benefit from structurally simple habitats and aggregations of winged insects around artificial light sources [4,[49][50][51]. Conversely, P. pulcher may have a more active approach to encountering dispersed insect prey amongst structurally diverse rock habitat (RW pers obs).…”
Section: Discussionmentioning
confidence: 99%
“…However, they differ in the strata used to forage. For example, Hemidactylus agrius and P. pollicaris are common in rocky outcrops, while Hemidactylus brasilianus and L. klugei are tree dwellers, and G. geckoides forages in the leaf litter (Vitt et al, 1995; Colli et al 2003; Rocha et al, 2005; Mesquita et al, 2006; Sousa et al, 2010; Recorder et al, 2012; Albuquerque et al, 2013; Passos et al, 2014). The similar nocturnal activity of the species may render similar insect prey and allow the infection by R. mottae , which seems to be a generalist parasite,…”
Section: Discussionmentioning
confidence: 99%
“…However, there is no records of insects as intermediate hosts for R. mottae , even though Lavoipierre & Lavoipierre (1966) found Periplaneta americana as intermediate host of R. hemidactyli in Singapore. Almeida et al (2008b) suggested that ants and termites could be intermediate hosts, because these insects are commonly found in lizard diets (Vitt et al, 1995, Colli et al, 2003, Rocha et al, 2005; Mesquita et al, 2006; Sousa et al, 2010; Recoder et al, 2012; Albuquerque et al 2013; Passos et al, 2014) which could possibly contribute to infections.…”
Section: Discussionmentioning
confidence: 99%
“…C annibalism among Tropical House Geckos (Hemidactylus mabouia) has been documented (Zamprogno and Teixeira 1998;Pombal and Pombal 2010;Rufino de Albuquerque et al 2013) but only Lyakurwa (2017) described such behavior and cannibalism in juveniles has not been reported. Herein we present an observation of cannibalism in two juvenile Tropical House Geckos and the first documented report of cannibalism in the species in Cuba.…”
Section: Reptiles and Amphibians C O N S E R V At I O N A N D N At U R A L H I S T O R Ymentioning
confidence: 99%